2020
DOI: 10.1111/mila.12294
|View full text |Cite
|
Sign up to set email alerts
|

Socially adaptive belief

Abstract: I clarify and defend the hypothesis that human belief formation is sensitive to social rewards and punishments, such that beliefs are sometimes formed based on unconscious expectations of their likely effects on other agents – agents who frequently reward us when we hold ungrounded beliefs and punish us when we hold reasonable ones. After clarifying this phenomenon and distinguishing it from other sources of bias in the psychological literature, I argue that the hypothesis is plausible on theoretical grounds a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
76
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(78 citation statements)
references
References 69 publications
2
76
0
Order By: Relevance
“…In line with recent work on the social organizational function of belief ( Boyer et al, 2015 ; Echterhoff et al, 2009 ; Gelpi et al, 2019 ; Jost et al, 2008 ; Mercier & Sperber, 2011 ; Williams, 2020 ), we suggest that causal models of delusions need to include dysfunction to coalitional cognition—that is, social cognitive processes involved in social influence, affiliation, interaction with groups, and the management of relationships. This approach has the advantage of better accounting for aspects of both the form and content of delusional beliefs as well as better reflecting the known function of the mesolimbic dopamine system—which is involved in the formation and maintenance of delusions and the management of social hierarchy, dominance, and cooperation.…”
supporting
confidence: 79%
See 1 more Smart Citation
“…In line with recent work on the social organizational function of belief ( Boyer et al, 2015 ; Echterhoff et al, 2009 ; Gelpi et al, 2019 ; Jost et al, 2008 ; Mercier & Sperber, 2011 ; Williams, 2020 ), we suggest that causal models of delusions need to include dysfunction to coalitional cognition—that is, social cognitive processes involved in social influence, affiliation, interaction with groups, and the management of relationships. This approach has the advantage of better accounting for aspects of both the form and content of delusional beliefs as well as better reflecting the known function of the mesolimbic dopamine system—which is involved in the formation and maintenance of delusions and the management of social hierarchy, dominance, and cooperation.…”
supporting
confidence: 79%
“… Cushman (2019) argued that the post hoc generation of reasons may not be efficient in itself for solving problems, but it allows people to apply the same reflective process to themselves and to others, again facilitating social coordination for problem-solving. Williams (2020) suggested that understanding the social function of belief better accounts for both its function and phenomenology but also better explains phenomena such as confabulation, positive illusions, and identity-protective cognition.…”
Section: Delusions As Dysfunction In Coalitional Cognitionmentioning
confidence: 99%
“…Importantly, the socially motivated ignorance here can be of at least two kinds. For some, it is clearly a consequence of the motivation to possess-and so advertise-certain beliefs because they are socially rewarded (Williams 2019). This corresponds most closely to Brennan's (2016) metaphor of political "hooligans," in contrast to political "hobbits" whose ignorance is largely driven by rational acquisitional ignorance.…”
Section: Rational Motivated Voter Ignorancementioning
confidence: 99%
“…4. 6 If such socially adaptive beliefs (Williams 2019) motivate one to avoid or distort information in tension with them, one's ignorance will be a case of socially motivated ignorance.…”
Section: Forms Of Motivated Ignorancementioning
confidence: 99%
“…It is important in this context to appreciate the important cultural, social and communal functions religions typically play, outside any claims about the metaphysics of reality -an aspect seldom appreciated in popular discourse. Indeed, belief may form a crucial social currency outside of any meta-physical claims on reality (Williams, 2019). The communal nature of religious activities, such as those based in a place of worship, increases the availability of social interactions and creates a sense of belonging between like-minded people (Debnam, Holt, Clark, Roth & Southward, 2013;Fatima, Sharif & Khalid, 2018), and can even hold together the foundational culture of a country (Abdulla, 2018).…”
Section: Introductionmentioning
confidence: 99%